Faktor-Faktor Yang Mempengaruhi Nilai Perusahaan Pada Perusahaan Manufaktur Di BEI - Vivi Novela, Sofia Prima Dewi (Jurnal Paradigma Akuntansi, 2019)
The purpose of this research is to present empirical evidence related value of the firm in manufacturing companies listed on Indonesia Stock Exchange. This research tested the influence of managerial ownership, capital structure, firm size, profitability and company growth on value of the firm. The sample of this was taken from 36 sample of the firm with the total 108 data from manufacture industry in period 2015-2017 using purposive sampling method. The data used are secondary data that disclose on the annual report and financial report of the company. Eviews 9.0 software is used to process data in this research. The result of this research indicate that capital structure and profitability have positive effect on value of the firm, while managerial ownership, firm size and company growth have no effect on income value of the firm